Association between PAX-9 promoter polymorphisms and hypodontia in humans - Peres, RCR; Scarel-Caminaga, R. M.; Santo, ARD; Line, SRP (Elsevier B.V., 2005)
Hypodontia, the congenital absence of one or a few teeth, is one of the most common alterations of the human dentition. The most common permanent missing teeth are the third molars, second premolars, and maxitlary lateral incisors. Hypodontia does not represent a serious public health problem, but it may cause masticatory and speech dysfunctions, and esthetic problems. PAX9 is believed to play an important rote in tooth development. It is expressed at initiation, bud, cap, and bell stages of odontogenesis. Mutations in PAX9 coding sequences have been implicated in autosomal dominant oligodontia affecting predominantly permanent molars and second premolars. Here, we report two polymorphisms in the promoter region of PAX9 gene that are associated with hypodontia. DNA was extracted from buccal epithelial. cells of 106 healthy Control individuals and of 102 unrelated individuals with hypodontia. PCR-RFLP was employed in the investigation of G-1031A and T-912C polymorphisms. Significant differences were obtained comparing Control and Test groups. Alleles G and T were found at a significant higher frequency in individuals with hypodontia, whereas alleles A and C were more frequent in Control subjects, p = 0.0094 and 0.0086, respectively. The GT haplotype was significantly more prevalent in the hypodontia group, white the AC haplotype was more frequent in the Control group. These results indicate that polymorphisms in the promoter region of PAX9 gene may have an influence on the transcriptional activity of this gene and are associated with hypodontia in humans. (c) 2005 Elsevier Ltd. AR rights reserved.
Keywords: hypodontia; PAX-9 gene; polymorphisms